2020
DOI: 10.1007/s12264-020-00478-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Purinergic P2X4 Receptors in Hippocampus Rescues Memory Impairment in Rats with Type 2 Diabetes

Abstract: Purinergic receptors have been reported to be involved in brain disorders. In this study, we explored their roles and mechanisms underlying the memory impairment in rats with type 2 diabetes mellitus (T2DM). T2DM rats exhibited a worse performance in the T-maze and Morris water maze (MWM) than controls. Microglia positive for P2X purinoceptor 4 (P2X4R) in the hippocampus were reduced and activated microglia were increased in T2DM rats. Long Amplicon PCR (LA-PCR) showed that DNA amplification of the p2x4r gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Lastly, we investigated whether SRC3 is important for hippocampus-dependent spatial memory in the Morris water maze [ 40 , 41 ]. Although the swimming speed was similar in WT and Src3 +/− mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we investigated whether SRC3 is important for hippocampus-dependent spatial memory in the Morris water maze [ 40 , 41 ]. Although the swimming speed was similar in WT and Src3 +/− mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, recent studies have shown the role of molecular signaling pathways involved in the protective effects of NOB in various diseases. Diabetes mellitus (DM) is a chronic metabolic disorder that glucose uptake undergoes impairment [58]. It is held that inflammatory factors participate in glucose uptake interference [59].…”
Section: Therapeutic and Biological Activities Of Nobmentioning
confidence: 99%
“…These data suggest that P2X4R is involved in the pathogenesis. In the CNS, P2X4R has been reported to be highly expressed in activated microglia, indicating that P2X4R may be involved in the inflammatory process [ 48 ]. Consistent with previous research, our immunofluorescence staining revealed that P2X4R is mainly expressed in activated microglia in the peri-hematoma region.…”
Section: Discussionmentioning
confidence: 99%